Protein complex prediction by date hub removal. (June 2018) - Pyrogova, Iana; Wong, Limsoon
Graphical abstract: Highlights: The date hub proteins tend to occur within the intersection of real overlapping protein complexes. We demonstrated that degree and transitivity can be used to predict a reliable list of date hub proteins. A complex discovery algorithm after removing date hubs from PPI networks recalls more overlapping complexes that were missed earlier. We proposed the "double-barrel strategy" to combine the complexes predicted before and after we remove date hubs. Abstract: Proteins physically interact with each other and form protein complexes to perform their biological functions. The prediction of protein complexes from protein–protein interaction (PPI) network is usually difficult when the complexes are overlapping with each other in a dense region of the network. To address the problem of predicting overlapping complexes, a previously proposed network–decomposition approach is promising. It decomposes a PPI network by e.g. removing proteins with high degree (hubs) which may participate in different complexes. This motivates us to examine a list of proteins, which bind their different partners at different time or at different location (viz. date hubs), manually collected from literature, for network decomposition. Results show that the CMC complex discovery algorithm after removing date hubs recalls more overlapping complexes that were missed earlier. Further improvement in performance is achieved when we predict date hub proteins based on simple network features and remove them from PPI networks.